Pregnancy-Associated Atypical Hemolytic-Uremic Syndrome - Antonio F. Saad; Jorge Roman; Aaron Wyble; Luis D. Pacheco (Thieme Medical Publishers, Inc., 2016)
Précis Introduction Early diagnosis of atypical uremic-hemolytic syndrome may be challenging during the puerperium period. Correct diagnosis and timely management are crucial to improve outcomes. Background Pregnancy-associated atypical hemolytic-uremic syndrome (p-aHUS) is a rare condition characterized by microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury. Triggered by pregnancy, genetically predisposed women develop the syndrome, leading to a disastrous hemolytic disease characterized by diffuse endothelial damage and platelet consumption. This disease is a life-threatening condition that requires prompt diagnosis and therapy. Case A 19-year-old G1P1 Caucasian female with suspicion of HELLP syndrome was treated at our facility for severe thrombocytopenia and acute kidney injury. A diagnosis of atypical uremic-hemolytic syndrome was later confirmed. The patient's condition improved with normalization of platelets and improvement in kidney function after 14 days of plasmapheresis. She was subsequently treated with eculizumab, a monoclonal antibody against C5. The patient tolerated well the therapy and is currently in remission. Conclusion Diagnosis of p-aHUS is challenging, as it can mimic various diseases found during pregnancy and the postpartum. Plasma exchange should be promptly initiated within 24 hours of diagnosis. Eculizumab has risen to become an important tool to improve long-term comorbidities and mortality in this group population.